Legal control of discretionary powers in Ghana: Lessons from English administrative law theory - Mensah, Kwadwo B. (Afrika Focus, 1998)
This paper develops along the following line. First, we shall attempt to explain what discretion is, why it has become very important in the modem administrative state, and the dangers that it poses in a democratic legal system. It then looks at the problems which have to be faced in justifying judicial review of discretion. It takes an in depth analysis of legal liberalism and functionalism. Aimed with these 'lenses', it attempts to explain the theoretical basis of two important Ghanaian cases, Re Akoto , and People's Popular Party v Attorney General (PPP v AG)'. It examines the provisions which regulate the use of discretionary powers in the Ghanaian 1993 Constitution and it looks at the choices we have to make from the various theories and the development of the administrative state in Ghana. KEY WORDS: functionalism, Ghana, judicial review, law, liberalism